THE STUDENTSâ€™ AND TEACHERSâ€™ PERCEPTION ON THE USE OF COMPUTER IN EFL CLASSROOMS - Anni Kristanti Yunandami; Muhammad Handi Gunawan (English Review: Journal of English Education, 2012)
Abstract: This research portrays the possibility of the computer used in the EFL classrooms, particularly in senior high school which focuses on the studentsâ€™ and teachersâ€™ perception on the use of computer in EFL classroom. The data from interview were transcribed and used to support the data from questionnaire. As an alternative learning device, computer helped the students to reach their goals in learning English, i.e.: the limited mastery ofÂ  vocabulary, the lack of tensesÂ  knowledge, focused on speaking and listening, the learning program was too difï¬cult to follow, no speech media (like microphone or headset), no equal chance in using computer because they had to share one computer with the whole class. For teacher, such strategy gave a different experience of way of teaching, a more creative method and material, a fun learning for the students, and many exposures of communicative dialogue.Â  Moreover, using computer in EFL classroom provided with some difï¬culties associated with the EFL situation, such as a large class sizes and mixed ability classrooms.Keywords:Â  Computer, Perception,Â  EFL Classroom